Transformer: A New Paradigm for Building Data-Parallel Programming Models - Wang, Peng; Meng, Dan; Han, Jizhong; Zhan, Jianfeng; Tu, Bibo; Shi, Xiaofeng; Wan, Le (IEEE MICRO, 2010)
Cloud computing drives the design and development of diverse programming models for massive data processing. the transformer programming framework aims to facilitate the building of diverse data-parallel programming models. transformer has two layers: a common runtime system and a model-specific system. using transformer, the authors show how to implement three programming models: dryad-like data flow, MapReduce, and All-Pairs.